Digital Signal Processing An Introduction with MATLAB and Applications - O$1 (BShea, Peter.s; Sadik, Amin Z.; Hussain, Zahir M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
In three parts, this book contributes to the advancement of engineering education and that serves as a general reference on digital signal processing. Part I presents the basics of analog and digital signals and systems in the time and frequency domain. It covers the core topics: convolution, transforms, filters, and random signal analysis. It also treats important applications including signal detection in noise, radar range estimation for airborne targets, binary communication systems, channel estimation, banking and financial applications, and audio effects production. Part II considers selected signal processing systems and techniques. Core topics covered are the Hilbert transformer, binary signal transmission, phase-locked loops, sigma-delta modulation, noise shaping, quantization, adaptive filters, and non-stationary signal analysis. Part III presents some selected advanced DSP topics.
Analog Signals and Systems -- Discrete and Digital Signals and Systems -- Selected Topics in Applied Signal Processing -- The Impact of Finite Wordlength Implementation -- Multirate Digital Signal Processing.
Keywords: Engineering; Systems engineering; Engineering; Signal, Image and Speech Processing; Circuits and Systems